2019
DOI: 10.3390/jdb7010004
|View full text |Cite
|
Sign up to set email alerts
|

The Forgotten Skeletogenic Condensations: A Comparison of Early Skeletal Development Amongst Vertebrates

Abstract: The development of a skeletogenic condensation is perhaps the most critical yet considerably overlooked stage of skeletogenesis. Described in this comprehensive review are the mechanisms that facilitate skeletogenic condensation formation, growth, and maintenance to allow for overt differentiation into a skeletal element. This review discusses the current knowledge of gene regulation and characterization of skeletogenic condensations in the chicken, mouse, zebrafish, and other developmental models. We limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 80 publications
1
42
0
Order By: Relevance
“…In addition, Yang et al [43] demonstrated that hypertrophic chondrocytes could trans-differentiate to osteoblasts and osteocytes by expressing Col1a1 and Osx during osteochondral bone formation. Although Ncam importantly regulates mesenchymal condensation during chondrogenesis [9], it also highly expresses in preosteoblastic cells during endochondral ossification [28,44]. Therefore, significant upregulation of Col1a1, Osx and Ncam by the chondrogenic induction at the late stage would be partly explained by occurrence of endochondral ossification in a mature chondrogenic cell population in OCI-iPSC constructs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Yang et al [43] demonstrated that hypertrophic chondrocytes could trans-differentiate to osteoblasts and osteocytes by expressing Col1a1 and Osx during osteochondral bone formation. Although Ncam importantly regulates mesenchymal condensation during chondrogenesis [9], it also highly expresses in preosteoblastic cells during endochondral ossification [28,44]. Therefore, significant upregulation of Col1a1, Osx and Ncam by the chondrogenic induction at the late stage would be partly explained by occurrence of endochondral ossification in a mature chondrogenic cell population in OCI-iPSC constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal condensation, i.e., densely packed aggregation of mesenchymal cells, occurs during the development of almost all tissues, including cartilage and bone [9]. Mesenchymal condensation is initiated by a signaling pathway involving cell adhesion molecules, such as Ncam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…placodes, anlagen) form-may have implications for expression of developmental plasticity and consequently variants available for selection (Pavlicev et al, 2011). In the skeletal system, the condensation stage is when many organs or structures establish proportions and interactions, so selection at this stage affects size, shape, number and integration of organs (Giffin et al, 2019;Atchley and Hall, 1991). In the skeletal system, the condensation stage is when many organs or structures establish proportions and interactions, so selection at this stage affects size, shape, number and integration of organs (Giffin et al, 2019;Atchley and Hall, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The early development of bones is studied as a 4-step process: migration of cells (e.g., neural crest cells or somite derivatives), epithelial-mesenchymal interactions, condensation formation, and differentiation (Giffin, Gaitor, & Franz-Odendaal, 2019;Hall & Miyake, 1995). The early development of bones is studied as a 4-step process: migration of cells (e.g., neural crest cells or somite derivatives), epithelial-mesenchymal interactions, condensation formation, and differentiation (Giffin, Gaitor, & Franz-Odendaal, 2019;Hall & Miyake, 1995).…”
mentioning
confidence: 99%